Applicability of the field research methods of landscape ecology and hidrology at Gödöllő-Isaszeg lake system on Rákos stream (methodological matters) - Komárominé Kucsák, Mónika; Bardóczyné Székely, Emőke (JOURNAL OF LANDSCAPE ECOLOGY, 2006)
In the first part of this year (2006) a group of research workers of the Dept. of Landscape Ecology (Szent István University) started to make an interdisciplinary landscape monitoring of Gödöllő-Isaszeg lake-system, that is placed in Rákos stream’s cathcment area. The field selection took to notice of the similarity type of landscape of the test sites. The main aim was the question of the generalitzation of field’s data. In the present article we describe the questions of forming landscape ecological units based on field work.
Keywords: Gödöllő-Isaszegi lake-system; Rákos stream’s catchment area; landscape ecology monitoring; interdisciplinary data of the conditions